Abortion and maternal mortality - Furman, Filip (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The objective of this chapter was to answer the question of whether the re strictiveness of abortion law affects maternal mortality, which varies greatly on a global scale due to cultural and geographical diversity. To improve (reduce) the maternal mortality rate, it is much more important to raise the overall standard of living in a country than to spend more on healthcare. Increasing access to abortion cannot be considered as a means of reducing maternal mortality. The use of statistical indicators not connected with qual itative knowledge of the cultural and economic context of a given region, without the support of medical research, has little methodological value and should not be the basis for international agencies to shape models according to which countries construct their law.